Transition of Therapeutic to Toxicological Effects of Certain Plant Alkaloids: A Critical Review Based on their Forensic Perspective - Kirubakarababu, Merlin; Samson Nesaraj, Arputharaj (Asian Journal of Chemistry, 2022)
The secondary metabolites have a significant property of therapy as well as toxicity. One among the secondary metabolite that is enormously present in plants is alkaloids. The occurrence of the alkaloid is found to be about 20% in the plants. These compounds have a useful therapeutic application in health disorders. On the other hand, they also cause toxicity to humans as well as animals. Their toxicity levels in humans may tend to affect the gastrointestinal and nervous systems. In this review, occurrence, synthesis and the toxicity levels of non-heterocyclic alkaloids viz. N-methyl tyramine and colchicine as well as heterocyclic alkaloids, viz. derivatives of pyrrolizidine (seneciphylline, echimidine), purine (caffeine, theobromine), indole (ergotamine, brucine) and glycoalkaloids (solanine, tomatine) are discussed. The detection of these alkaloids by chromatographic techniques is also underlined.